KONTRADIKSI HADIS LARANGAN BERDIRI UNTUK ORANG LAIN DAN PENYELESAIANNYA PERSEPEKTIF METODE MUKHTALIF AL-SHAFI’Ī.docx - Moh Imron; Alwi Shobri (AL-BAYAN INSTITUTE, 2025)
Standing respectfully is one of the customs that is usually carried out by the Muslim community, especially in Indonesia. However, this caused a polemic among the people after learning of the hadith of the Prophet which explained that anyone who likes others to stand up for him should prepare his place in Hell. This hadith shows the meaning of the prohibition to stand respectfully, but on another occasion the Prophet stood up immediately when Fatima came. This hadith contradiction then requires understanding and study to find common ground for the contradictions of these two propositions with the aim of compromising the contradictions in the two propositions to maintain the authenticity of the Prophet's hadith. The methodology used in this study is a qualitative method and literature review. Data collection techniques with the documentation method. The results of this study conclude that the hadith about the prohibition of standing respectfully is not contradictory even though it appears to be contradictory. However, the hadith which prohibits standing respectfully shows a general meaning so that standing respectfully in any form is not permissible. The hadith which shows the meaning of the permissibility of standing respectfully contains a special meaning, namely being allowed to stand in the context of welcoming as the Prophet taught when welcoming Fatimah